2018
DOI: 10.1590/1980-5373-mr-2017-0795
|View full text |Cite
|
Sign up to set email alerts
|

Damping of the Woodwind Instrument Reed Material Arundo donax L

Abstract: The viscoelastic properties (E', G', tanΦ, δ) of Arundo donax (AD) and a polypropylene-beech fiber composite (PPC) were measured from RT to 580K for various frequencies and strains. E' of AD varies between 5250-6250MPa depending on ageing at RT while E'(RT)=2250MPa of PPC is signifcantly lower. E' of the AD is higher than E' of PPC in the whole investigated temperature range with the exception of AD after a heat treatment up to 575K. Damping spectra exhibit peaks around 340K (Q=234kJ/mol) and 415K for the PPC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The average values were 4.79 ± 0.7 GPa and 5.23 ± 1.25 GPa which are in trend with our results obtained on small samples. Weidenfeller et al [ 8 ] compared the storage modulus of two Arundo Donax samples by DMA and found a value of 5.25 GPa and 6.25 GPa. Although the static modulus of elasticity is similar conceptually to the storage modulus, values will differ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average values were 4.79 ± 0.7 GPa and 5.23 ± 1.25 GPa which are in trend with our results obtained on small samples. Weidenfeller et al [ 8 ] compared the storage modulus of two Arundo Donax samples by DMA and found a value of 5.25 GPa and 6.25 GPa. Although the static modulus of elasticity is similar conceptually to the storage modulus, values will differ.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of papers report on elasticity parameters of natural reed materials. In [ 7 , 8 ], the longitudinal elasticity modulus of natural cane was measured, and values between 4 and 7 GPa are reported. Taillard et al [ 9 ] pointed out the importance of the bending of the reed in the direction perpendicular to its axis, and presented modelling results using different mechanical parameters in the directions along and perpendicular to the length axis of the reed.…”
Section: Introductionmentioning
confidence: 99%
“…It forms dense stands, for example, in the Camargue in southern France, where it is often planted as a windbreak. The giant reed is also called the clarinet reed because the reeds for woodwind instruments such as clarinets, oboes, saxophones, and bagpipes are made from its stem [ 46 ].…”
Section: Educational Trail About Biomimeticsmentioning
confidence: 99%
“…With regards to its range of applications, Arundo donax stem is used for the production of musical woodwind instruments [19,20], fences, trellises, stakes for plants, windbreaks, sun shelters [21], as a fiber source for printing paper [22], and as a source of biomass for chemical feedstocks and for energy production. In particular, Papazoglou et al [23] evaluated the growth of Arundo donax L. on soil irrigated with cadmium and nickel solutions to evaluate the impact of these heavy metals on its growth and photosynthesis.…”
Section: Introductionmentioning
confidence: 99%